2019
DOI: 10.3390/bs9070077
|View full text |Cite
|
Sign up to set email alerts
|

Heroin Overdose-Related Child and Adolescent Hospitalizations: Insight on Comorbid Psychiatric and Substance Use Disorders

Abstract: Objective: To evaluate the association between psychiatric comorbidities, substance use disorders and heroin overdose-related hospitalizations (HOD). Next, to understand the demographic trend of HOD hospitalizations and comorbidities. Methods: Using the Nationwide Inpatient Sample (NIS), we included 27,442,808 child and adolescent hospitalizations, and 1432 inpatients (0.005%) were managed primarily for HOD. The odds ratio (OR) of the association of variables in HOD inpatients were measured using a logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We also found that POD-related hospitalizations had comorbid SUDs with opioids, cannabis, and tobacco, with cannabis being the most prevalent substance used due to the rising use of cannabis among the pediatric population [15]. Also, an inpatient study found a higher prevalence of tobacco (36.8%) and cannabis (28.5%) use disorders among pediatric patients hospitalized for heroin overdoses [16].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that POD-related hospitalizations had comorbid SUDs with opioids, cannabis, and tobacco, with cannabis being the most prevalent substance used due to the rising use of cannabis among the pediatric population [15]. Also, an inpatient study found a higher prevalence of tobacco (36.8%) and cannabis (28.5%) use disorders among pediatric patients hospitalized for heroin overdoses [16].…”
Section: Discussionmentioning
confidence: 99%
“…Heroin is a highly addictive opioid drug with a high risk of overdose and death for users. A trend study from 2010 to 2014 revealed that approximately 20% of emergency department visits attributed to heroin overdose, and each year, these numbers were rising (Queeneth et al, 2019). Studies also revealed that nearly 8,986 adolescents have died from heroin overdose in the past 18 years in the US (Centers for Disease Control and Prevention, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the numerous strategies recommended to deal with the phenomenon, among the most cited, it emerges the clear urge to enhance training and information for both healthcare providers and patients [ 5 , 12 , 14 , 31 , 41 , 45 , 49 , 52 , 53 , 54 , 57 ]. This is essentially related to the recommendation to prevent rather than implement subsequent containment and corrective action [ 12 , 31 , 36 , 40 , 42 , 46 , 54 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other strategies suggested by multiple contributions are to implement programs to treat opioid addiction [ 4 , 5 , 34 , 40 , 46 ] and increase research, grants, and funding in the sector [ 36 , 46 , 48 , 50 , 56 ]. In addition, many contributions support the need to implement medical care [ 31 , 36 , 42 , 43 , 46 ] and increase the prescription and use of naloxone [ 12 , 31 , 33 , 42 , 43 ]. Cordes [ 12 ] reports the results of his study as follows:…”
Section: Resultsmentioning
confidence: 99%